An FEVR-associated mutation in ZNF408 alters the expression of genes involved in the development of vasculature. (1st August 2018) - Karjosukarso, Dyah W; van Gestel, Sebastianus H C; Qu, Jieqiong; Kouwenhoven, Evelyn N; Duijkers, Lonneke; Garanto, Alejandro; Zhou, Huiqing; Collin, Rob W J
Abstract: Familial exudative vitreoretinopathy (FEVR) is an inherited retinal disorder hallmarked by an abnormal development of retinal vasculature. A missense mutation in ZNF408 (p.H455Y) was reported to underlie autosomal dominant FEVR in a large Dutch family, and ZNF408 was shown to play a role in the development of vasculature. Nonetheless, little is known about the molecular mechanism of ZNF408 -associated FEVR. To investigate this, an in vitro model of ZNF408 -associated FEVR was generated by overexpressing wild-type and p.H455Y ZNF408 in human umbilical vein endothelial cells. Cells overexpressing mutant ZNF408 were unable to form a capillary-like network in an in vitro tube formation assay, thereby mimicking the clinical feature observed in patients with FEVR. Intriguingly, transcriptome analysis revealed that genes involved in the development of vasculature were deregulated by the p.H455Y mutation. Chromatin immunoprecipitation showed that p.H455Y ZNF408 has reduced DNA-binding ability, as compared to the wild-type protein. The fact that the p.H455Y mutation disrupts the expression of genes important for the development of vasculature sheds further light on the molecular mechanisms underlying ZNF408 -associated FEVR.